2014
DOI: 10.3389/fnint.2014.00067
|View full text |Cite
|
Sign up to set email alerts
|

LATER models of neural decision behavior in choice tasks

Abstract: Reaction time has been increasingly used over the last few decades to provide information on neural decision processes: it is a direct reflection of decision time. Saccades provide an excellent paradigm for this because many of them can be made in a very short time and the underlying neural pathways are relatively well-known. LATER (linear approach to threshold with ergodic rate) is a model originally devised to explain reaction time distributions in simple decision tasks. Recently, however it is being extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 56 publications
1
25
1
Order By: Relevance
“…Altering the prior probability S 0 should result in a specific change, a 'swivel', in the subjects' RT distribution; and indeed this is what was observed [13]. The LATER model itself has been recently reviewed elsewhere [1,2,17].…”
Section: The Later Modelmentioning
confidence: 74%
“…Altering the prior probability S 0 should result in a specific change, a 'swivel', in the subjects' RT distribution; and indeed this is what was observed [13]. The LATER model itself has been recently reviewed elsewhere [1,2,17].…”
Section: The Later Modelmentioning
confidence: 74%
“…The finding of no significant difference in the event start for the trials supports the theory that the effect of DA is not related to basic idiosyncratic between group differences. Because there are no between group differences related to the decision signal/onset of the trial, there is no interest in testing additional models for a deeper analysis (as described in Carpenter, ; Carpenter, Redd & Anderson, ; Carpenter & Williams ; Noorani, ). The preliminary analysis showed that the average latency in the CG was below 275 ms, and the average latency in the EG was above 275 ms, when both aggregated data and raw data were considered.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the model in Noorani and Carpenter (2013) does not incorporate a late decision process and thereby it explains all errors as inhibition failures. On the other hand, lateral inhibition models (Cutsuridis et al, 2007;2014;Cutsuridis, 2015) explain errors as the result of connected accumulators that represent pro-and antisaccades, without the intervention of a third inhibitory unit. Accordingly, an error occurs when a voluntary action does not inhibit a reflex-like prosaccade.…”
Section: Early and Late Errors On Antisaccade Trialsmentioning
confidence: 99%